Colombian university journalism as a virtual stage for transitions toward acts of memory and peace - Rendon Cardona, Paula Andrea; Rivera Henao, Mauricio; Betancurth Becerra, Carlos Mario; Aristizábal, Cesar Alberto; Páez Valdéz, Julián Enrique (Frontiers in Education, 2022)
This article is concerned with narrating the research-creation experience that emerged from the CAPAZ project (Analytical Center for University Productions in the Framework of Conflict). It aims to account for the emergence of the transmedia web platform “RUTAS: University Peace Stories in Colombia,” based on the analysis of the media representations produced by the national opinion sector of university journalism that are concerned with peace narratives from 2000 to 2021. A mixed methodological approach and an experimental scheme with Big Data techniques derived from an automated lexicometric analysis led to the implementation of a strategy for creating pedagogical narratives that categorized the results obtained. Thus, RUTAS was born as an exercise involving the deployment of knowledge and creative skills around the notions of design as a possibility and hypermediality as a scenario of digital and interactive stories, housed in virtual, cultural, and open platforms that would give rise to multiple representations and media appropriations in the field of communication and education.